(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of this research is to show the level of banking leadership trends in the importance of organizational confidence and its reflection in the dimensions of the strategic position the research was applied in a bank (Al- Mansour Investment, Business Bay), and the Questionnaire Was adopted as a tool to collect data and information from the number of the sample (15) who are in allocation (Department Manager, Department Manager Department Manager, Division Officer, Unit Officer) and he used the statistical program (spss) to calculate (standard deviation, arithmetic mean, percentages, regression, analysis,F-test coefficient of determination R2, Coefficieent, square Kay and the research reached a number of conclusions, the most prominent of which are:- there is an effect of total confidence in achieving the strategic position of the two surveyed banks in its dimensions, and the impact percentage Was (88%) there are also differences in the sample responses about the paragraphs of the questionnaire combined according to personal variables, academic qualification, number of years of service. While these differences do not exist within the job position, in addition to that the level of trends of banking leaders towards the importance of organizational trust and strategic position was to a high degree